Implementasi Kebijakan Pembuatan Kartu Keluarga di Kecamatan Megang Sakti Kabupaten Musi Rawas - Dede Mardiono Hz; Novia Kencana; Muhammad Quranul Kariem (CV The Journal Publishing, 2022)
The problem of public services provided by government officials is the main complaint of the community, because the service process is often not in accordance with established procedures. The research method used is qualitative. The results of the discussion of this study are (1) Communication has not run optimally, because there is no socialization carried out directly by the District to the community. (2) Resources are also not running well due to limited skills and knowledge in terms of science and technology, supporting facilities and infrastructure also do not support the activities of this program. (3) The disposition of this indicator, the researcher found that there were deviations made by the implementing party during the process of making the Family Card. (4) Bureaucratic Structure in this indicator The Bureaucratic Structure is clear because of the availability of SOPs and existing mechanisms in the implementation of the program. The conclusion of this study is that the Family Card program in Megang Sakti District, Musi Rawas Regency has not run optimally. Suggestions in this research is that the District should conduct socialization to the community regarding the Making of Family Cards, the Central Government should provide training and guidance to the implementers of this policy program with the theme of ethics and behavior that aims to minimize illegal fees.